Disorganization of retinal inner layers correlates with ellipsoid zone disruption and retinal nerve fiber layer thinning in diabetic retinopathy - Nadri, Gauhar; Saxena, Sandeep; Stefanickova, Jana; Ziak, Peter; Benacka, Jozef; Gilhotra, Jagjit S; Kruzliak, Peter (Journal of diabetes and its complications, 2019)
PURPOSE: To study the correlation between disorganization of inner retinal layer (DRIL) and macular thickness parameters, ellipsoid zone (EZ) disruption and retinal nerve fiber layer (RNFL) thickness on spectral domain optical coherence tomography (SD-OCT) in diabetic retinopathy (DR), for the first time. METHODS: A tertiary care center-based cross-sectional study was undertaken. One hundred and four consecutive study subjects of type 2 diabetes mellitus were included: diabetes mellitus with no retinopathy (No DR) (n = 26); non-proliferative DR (NPDR) (n = 26); proliferative DR (PDR) (n = 26) and healthy controls (n = 26). Best Corrected Visual Acuity (BCVA) was measured on the logarithm of the minimum angle of resolution (logMAR) scale. Clinician-friendly, SD-OCT based, grading systems were created for DRIL and EZ disruption, within the macular cube. DRIL was graded as: grade 0, DRIL absent; and grade 1, DRIL present. EZ disruption was graded as; Grade 0: Intact EZ; Grade 1: Focal disruption and Grade 2: Global disruption. Every study subject underwent RNFL thickness analysis. RESULTS: DRIL was significantly associated with increase in severity of DR.Pearson correlation analysis showed significant positive correlation between DRIL and CST CAT and grades of EZ disruption . However, a significant negative correlation was found between DRIL and RNFL thickness . CONCLUSION: Presence of DRIL correlates with severity of DR, EZ disruption and RNFL thinning.
Keywords: macula lutea; Humans; diabetická retinopatie; lidé středního věku; Female; Imaging biomarkers; optická koherentní tomografie; Macular thickness parameters; Retinal nerve fiber layer (RNFL) thickness; lidé; Disorganization of inner retinal layer (DRIL); retina; Diabetes Mellitus, Type 2; Retina; Spectral domain optical coherence tomography (SD-OCT); nervová vlákna; ženské pohlaví; Diabetic retinopathy; Macula Lutea; Male; Middle Aged; Diabetic Retinopathy; Cross-Sectional Studies; Nerve Fibers; Tomography, Optical Coherence; mužské pohlaví; diabetes mellitus 2. typu; Visual Acuity; průřezové studie; zraková ostrost